Relevance of Humanistic Education in Faculties of Experimental Sciences: A Comprehensive Study - Gimenez Armentia, Pilar; Viñado Otero, Fernando (European Public & Social Innovation Review, 2025)
Introduction: The university has evolved to adapt to recent changes, prioritizing specialization at the expense of holistic education. This article examines how this transformation has created a gap between the humanities and scientific disciplines, displacing critical reflection with efficiency. Our objectives are to explore the historical foundations of the university to preserve its essence and to argue the importance of comprehensive education through a concrete case in the Faculty of Experimental Sciences at Universidad Francisco de Vitoria, which integrates humanities subjects and interdisciplinary activities into its programs. Methodology: The research conducted has been descriptive, using both quantitative and qualitative experimental methodologies in line with the proposed objectives. The empirical study was conducted with 1690 students, showing that comprehensive and humanistic education improves learning in experimental sciences. Conclusions: The results highlight the need for innovative methodologies that foster integral knowledge and the intersection between science and the humanities, emphasizing the importance of future scientists studying humanities subjects to develop a broader understanding of reality and recognize the limits of the scientific method.